An autophagy assay reveals the ESCRT-III component CHMP2A as a regulator of phagophore closure - Yoshinori Takahashi (Nature Portfolio, 2018)
During autophagy, phagophores elongate to form double-membrane vesicles but the mechanism behind their closure is unknown. Here, the authors develop an autophagy assay and find a role for the endosomal sorting complexes required for transport component CHMP2A as a phagophore closure regulator.